The theory of post-industrial society - Wan Fariza Alyati Wan Zakaria; Buaben, Jabal M. (Penerbit Universiti Kebangsaan Malaysia, 2021)
This articles attempts at firstly looking at Daniel Bell’s background and thereafter discussing selected themes of his thoughts regarding to the future society. This will be done by scrutinising his main intellectual works, particularly with regards to his theoretical analysis on the future society, namely the post-industrial society. The books are The Coming of Post-Industrial Society: A Venture in Social Forecasting (1973), The Cultural Contradictions of Capitalism (1976) and The End of ideology (1960). Other materials written by Bell were also consulted wherever related. The methodology applied in this article is content analysis whereby key words related to post-industrial society such as knowledge, change and technology were analysed, criticised and thereafter used to understand the underlying framework or worldview that constitute the scholar’s ideas. The discussion on the results of this worldview suggests that the logical movement of history works in its deterministic way in which problems faced by the societies such as injustices, inequalities, poverty, racial divisions and so on will cease away and that the society will move towards a better and more desirable order. It is hoped that this article would contribute significantly to deepening our understanding on the discourse of the post-industrial society, and how it relates to our current context.